Stylistic formation in the book “Sayd Alkhatir” by Ibn Al-Jawzi (d. 597 AH): Phonetic level: The rhyme as a model - Alhammadi, Aisha; Bataher, Bin Issa (Al-Adab Journal, 2024)
rhyme is one of the terms in which the aspect of phonetic features was taken into account in the structure of the prose text, as it is one of the innovative improvements that were common in all the arts of prose: such as letters, wills and shrines, as rhyme is a rhythmic phenomenon that has its aesthetic value and its impact on the text. The early Arabs were known for their eloquence and care for this color of Badi'a for them, especially the preachers of the pre-Islamic era because of its musical timbre, ringing of minds, and arousing attention.The arts of prose developed in the Abbasid era, and writers expanded in the use of rhyme and alliteration, so this wonderful color became one of the fixed traditions in writing letters and prose discourse, specifically the Diwaniyah and Brotherhood letters, so these letters were characterized by verbal elegance and vocal coloring, so they were a prominent stylistic feature in their works, and with the spread of preaching councils and religious lessons in Baghdad, rhyme became one of the most prominent means of expression and the arts of saying they have, but one of the most important means of influencing and attracting people.Accordingly, this study came in an attempt to reveal the stylistic formation of the phrases of the most famous preachers and scholars of Baghdad in the sixth century AH, and the choice fell on the book " Sayd Alkhatir " by Ibn Al-Jawzi, Ibn Al-Jawzi was famous for his ingenuity in preaching rhyme, and says golden: "As for the verbal rhyme, it has a strong queen, and if improvised, he excelled".In this study, we relied on the descriptive analytical approach, with the help of the statistical method, which provided us with some data that may help us determine the density and images of rhyme, and its role in the stylistic formation of the text.